Prevalence and molecular epidemiology of Clostridium difficile infection in Indonesia. (July 2017) - Collins, D.A.; Gasem, M.H.; Habibie, T.H.; Arinton, I.G.; Hendriyanto, P.; Hartana, A.P.; Riley, T.V.
Abstract: Clostridium difficile has not been studied in detail in Asia, particularly Southeast Asia. We thus performed a prevalence study across four hospitals in Central Java province, Indonesia. Stool samples were collected from patients with diarrhoea and tested by enzyme immunoassay for glutamate dehydrogenase (GDH) and toxin A/B (C DIFF QUIK CHEK COMPLETE, TechLab). Specimens were cultured and molecular typing was performed. In total, 340 samples were tested, of which 70 (20.6%) were GDH positive, with toxin detected in 19 (5.6%). Toxigenic C. difficile was isolated from 37 specimens (10.9%), while a further 36 (10.6%) nontoxigenic isolates were identified. The most common strain was ribotype 017 (24.3% of 74 isolates), followed by nontoxigenic types QX 224 (9.5%), and QX 238 and QX 108 (both 8.1%). The high prevalence of C. difficile highlights a need for ongoing surveillance of C. difficile infection in Indonesia.